Silver nanoparticles against Staphylococcus aureus resistant to meticillin: a literature review - Schramm Oliveira, Pâmella; Balreira, Flavia; Sagrillo, Michele; Zanella, Ivana; Ourique, Aline (Disciplinarum Scientia | Naturais e Tecnológicas, 2019)
The Methicillin-resistant Staphylococcus aureus (MRSA) represents a critic risk to public health because it has resistance to multiple antimicrobial agents and is one of the most common nosocomial pathogens. Consequently, researches to develop or modify antimicrobial compounds to improve bactericidal against the potential strains of MRSA have been grouwing. In this context, this study aimed to conduct a literature review about the antimicrobial activity against MRSA of silver nanoparticles (AgNPs) and discuss the main results. The survey was conducted in the ScienceDirect database, where the descriptors used were “silver nano * and MRSA”. Based on the results, we can conclude that the antimicrobial effects of the AgNPs against MRSA are promising in several areas, as these did not cause damage to healthy cells and caused no observable side effects.